A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
If ƒ(x)=−10x−6ƒ(x)=−10x−6, then ƒ^−1(x)=
anonymous
 one year ago
If ƒ(x)=−10x−6ƒ(x)=−10x−6, then ƒ^−1(x)=

This Question is Closed

Astrophysics
 one year ago
Best ResponseYou've already chosen the best response.0To find the inverse: Replace f(x) with y Switch x's and y's, so put x where y is and x where y is. Solve for y Replace y with f^1(x)

LynFran
 one year ago
Best ResponseYou've already chosen the best response.2first rewrite the function as an equation y=10x6 solve for x y+6=10x (y+6)/10=x then write f^1(y) f^1(y)=(y+6)/10 or f^1(x)=(x+6)/10 then check.. f(f^1(x))=10(f^1(x))6 can u finish from here...

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0sorry i just realized i typed it wrong

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0its if ƒ(x)=−10x−6, then ƒ^−1(x)=

LynFran
 one year ago
Best ResponseYou've already chosen the best response.2i know ... thats the same function i did above...

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0okay so do i solve that?

Astrophysics
 one year ago
Best ResponseYou've already chosen the best response.0All the steps are given, please try it out.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.